Students’ Usage and Access to Multimedia Learning Resources in an Online Course with Respect to Individual Learning Styles as Identified by the VARK model - Kišiček, Sanja (Array, 2012)
We present a research on students’ learning styles and their learning activity with respect to multimedia learning resources in a virtual learning environment within a Moodle online course. We investigate the relation between learning styles based on sensory modality and their learning activity regarding different types of multimedia resources.